Analisis Pesan Dakwah Dalam Film Cinta Subuh Oleh Rumah Produksi Falcon Picture - Aldyansyah .; Achmad Syarifudin; Muslimin Muslimin (CV. ITTC INDONESIA, 2026)
This research is motivated by the perspective that film can serve as an effective medium for conveying da’wah messages, as it can be easily received by the public. The film Cinta Subuh is one example that has inspired many people. Through film as a medium, da’wah messages can be delivered without significant limitations. The problem formulation in this study is: what are the da’wah messages contained in the film Cinta Subuh produced by Falcon Pictures? The purpose of this study is to identify and analyze the da’wah messages presented in the film Cinta Subuh by Falcon Pictures. This study employs a qualitative research approach. There are two types of data sources used: primary data, consisting of audio and visual elements found in the film, and secondary data, including books, theses, journal articles, and other relevant literature. Data collection techniques include documentation and observation of the film Cinta Subuh. The data analysis technique uses descriptive analysis through John Smith’s interactive model, which consists of: (1) the level of reality, including appearance codes and environmental codes, and (2) the level of representation, which focuses on character codes.The results of the study show that the film Cinta Subuh contains da’wah messages in three aspects. First, the message of Aqidah, such as the importance of reading the Qur’an to calm the heart. Second, the message of Sharia, demonstrated through the importance of performing prayers on time. Third, the message of Akhlaq, reflected in the characters’ behavior, such as advising one another in goodness.